Pengaruh Jumlah Penduduk, Jumlah Wisatawan dan Jumlah Hotel terhadap PAD Provinsi Jawa Timur - Septiyani, Septiyani (Jurnal Ekonomika : INDEPENDEN, 2024)
This research aims to determine the impact of population, number of tourists and number of accommodation on people's income in the East Java Region in 2018-2022. This exploration uses a quantitative methodology and utilizes optional information obtained from the East Java Regional Focus Measurement Organization. The method used in this research is panel data regression. The results of this research show that one factor, namely the quantity of tourists, makes a very large positive difference, while the population and number of accommodation factors do not necessarily affect local revenue in the East Java Region in 2018-2022.